Risperidone Toxicity on Human Blood Lymphocytes in Nano molar Concentrations - Yousefsani, Bahareh Sadat; Salimi, Ahmad; Imani, Farnaz; Ramezani, Maral; Shirani, Kobra; Seydi, Enayatollah; Pourahmad, Jalal (Drug Research, 2022)
Risperidone is an atypical antipsychotic drug used for the pharmacotherapy of psychiatric disorders. Some reports indicate that risperidone is toxic to various systems of the body, including the immune system. This study evaluated the toxicity effect of risperidone on human blood lymphocytes. To achieve this aim, lymphocytes were isolated using Ficoll paque plus. The results showed that risperidone (12, 24 and 48 nM) causes toxicity in human blood lymphocytes by increasing the level of intracellular reactive oxygen species (ROS), damage to lysosomal membrane, the collapse of the mitochondrial membrane potential (MMP), and increased extracellular oxidized glutathione (GSSG). Also, exposure of human blood lymphocytes to risperidone is associated with a decrease in intracellular glutathione (GSH) levels. Finally, it could be concluded that oxidative stress is one of the mechanisms of risperidone-induced toxicity in human blood lymphocytes.
Keywords: Risperidone; Antipsychotic Agents; Immunotoxicity; Oxidative Stress, Lysosomes; Mitochondria